A sala de aula invertida integrada às tecnologias digitais na formação continuada de professores que atuam no ensino médio integral - Medeiros, Ádila de Lima Ferreira (2020)
The expanding scenario of the use of digital information and communication technologies has been increasingly narrowing the distance between connections in physical and virtual environments, reflecting directly on education and, in a special way, in the teachers’ training, who need to take on new attitudes regarding the use of technologies, breaking up with the very culture of a traditionally applied pedagogy. Given the above, this study sought to focus on continuing the teacher education and integration of the inverted classroom (IAS) with digital resources, answer the following research question: what are the contributions of the inverted classroom as an experimental model of continuing education for teachers working in integral High School? In order to achieve answers to the question, it was defined as a general objective to analyze the contributions of the inverted classroom as an experience of continuing education of Integral High School’s teachers of a public school in the city of Extremoz / RN. And as specific objectives: 1) Conduct a survey on the real conditions and needs for the implementation of the experiment; 2) Develop a continuous training course based on IAS integrated with digital technologies teachers; 3) Check the teachers’ perception about the training process and the application of IAS; 4) Produce a didactic guide based on the experience of continuing education. For the qualitative research paradigms and the action research method were followed, based on Thiliollent (2011). The theoretical framework was built from two basic categories: Teacher Education, in the light of scholars, Tardif (2011), Imbernón (2011), Libâneo (2011), and so on; and the inverted classroom from Moran (2015), Bergmann and Sams (2018) and Valente (2014). The results showed that IAS is a methodology with great potential to be used in teacher training courses, however it’s essential that it is applied within a time that allows teachers to have a significant appropriation, especially when integrated with the development of digital skills. Despite the difficulties imposed by an educational context in times of Covid -19 pandemic, teachers made use of IAS in an interdisciplinary proposal, taking advantage of the experiences of continuing education and giving new meaning to their practices. Finally, through all the possibilities conceived in this research, including the production of a didactic guide, it’s expected to provide important subsides, mainly for the education of the State of Rio Grande do Norte and of school institutions themselves in the valorization, maintenance and restructuring of the permanent processes of improvement of its professionals.